Beyond Gut Instinct: Metabolic Short-Chain Fatty Acids Moderate the Pathogenesis of Alphaherpesviruses - Poelaert, Katrien C. K.; Van Cleemput, Jolien; Laval, Kathlyn; Descamps, Sarah; Favoreel, Herman W.; Nauwynck, Hans J. (Frontiers in Microbiology, 2019)
Short-chain fatty acids (SCFA), such as sodium butyrate (SB), sodium propionate (SPr), and sodium acetate (SAc), are metabolic end-products of the fermentation of dietary fibers. They are linked with multiple beneficial effects on the general mammalian health, based on the sophisticated interplay with the host immune response. Equine herpesvirus 1 (EHV1) is a major pathogen, which primarily replicates in the respiratory epithelium, and disseminates through the body via a cell-associated viremia in leukocytes, even in the presence of neutralizing antibodies. Infected monocytic CD172a+ cells and T-lymphocytes transmit EHV1 to the endothelium of the endometrium or central nervous system, causing reproductive or neurological disorders. Here, we questioned whether SCFA have a potential role in shaping the pathogenesis of EHV1 during the primary replication in the URT, during the cell-associated viremia, or at the level of the endothelium of the pregnant uterus and/or central nervous system. First, we demonstrated the expression of SCFA receptors, FFA2 and FFA3, within the epithelium of the equine respiratory tract, at the cell surface of immune cells, and equine endothelium. Subsequently, EHV1 replication was evaluated in the URT, in the presence or absence of SB, SPr, or SAc. In general, we demonstrated that SCFA do not affect the number of viral plaques or virus titer upon primary viral replication. Only SB and SPr were able to reduce plaque latitudes. Similarly, pretreatment of monocytic CD172a+ cells and T-lymphocytes with different concentrations of SCFA did not alter the number of infected cells. When endothelial cells were treated with SB, SPr, or SAc, prior to the co-cultivation with EHV1-inoculated mononuclear cells, we observed a reduced number of adherent immune cells to the target endothelium. This was associated with a downregulation of endothelial adhesion molecules ICAM-1 and VCAM-1 in the presence of SCFA, which ultimately lead to a significant reduction of the EHV1 endothelial plaques. These results indicate that physiological concentrations of SCFA may affect the pathogenesis of EHV1, mainly at the target endothelium, in favor of the fitness of the horse. Our findings may have significant implications to develop innovative therapies, to prevent the devastating clinical outcome of EHV1 infections.